Mutation Analysis of the RAD51C and RAD51D Genes in High-Risk Ovarian Cancer Patients and Families from the Czech Republic - Janatova, Marketa; Soukupova, Jana; Stribrna, Jana; Kleiblova, Petra; Vocka, Michal; Boudova, Petra; Kleibl, Zdenek; Pohlreich, Petr (PloS one, 2015)
Recent studies have conferred that the RAD51C and RAD51D genes, which code for the essential proteins involved in homologous recombination, are ovarian cancer (OC) susceptibility genes that may explain genetic risks in high-risk patients. We performed a mutation analysis in 171 high-risk BRCA1 and BRCA2 negative OC patients, to evaluate the frequency of hereditary RAD51C and RAD51D variants in Czech population. The analysis involved direct sequencing, high resolution melting and multiple ligation-dependent probe analysis. We identified two (1.2%) and three (1.8%) inactivating germline mutations in both respective genes, two of which (c.379_380insG, p.P127Rfs*28 in RAD51C and c.879delG, p.C294Vfs*16 in RAD51D) were novel. Interestingly, an indicative family cancer history was not present in four carriers. Moreover, the ages at the OC diagnoses in identified mutation carriers were substantially lower than those reported in previous studies (four carriers were younger than 45 years). Further, we also described rare missense variants, two in RAD51C and one in RAD51D whose clinical significance needs to be verified. Truncating mutations and rare missense variants ascertained in OC patients were not detected in 1226 control samples. Although the cumulative frequency of RAD51C and RAD51D truncating mutations in our patients was lower than that of the BRCA1 and BRCA2 genes, it may explain OC susceptibility in approximately 3% of high-risk OC patients. Therefore, an RAD51C and RAD51D analysis should be implemented into the comprehensive multi-gene testing for high-risk OC patients, including early-onset OC patients without a family cancer history.
Keywords: exony; protein BRCA2; DNA-Binding Proteins; rodina; Humans; sekvence nukleotidů; DNA vazebné proteiny; Family; mutační analýza DNA; Molecular Sequence Data; molekulární sekvence - údaje; BRCA1 Protein; Female; rizikové faktory; nádory vaječníků; Ovarian Neoplasms; Exons; DNA, Complementary; lidé; komplementární DNA; DNA Mutational Analysis; ženské pohlaví; Base Sequence; Genetic Predisposition to Disease; genetická predispozice k nemoci; protein BRCA1; Czech Republic; Introns; Genes, Neoplasm; geny nádorové; BRCA2 Protein; Česká republika; introny; Risk Factors